EVALUATION OF ANTIOXIDANT ACTIVITY OF YELLOW COCONUT (Cocos nucifera L) USING THE DPPH METHOD: EVALUASI AKTIVITAS ANTIOKSIDAN KELAPA KUNING (Cocos Nucifera L) DENGAN METODE DPPH - Baihaqi; Fatahu; Sakir; Andi Laila Nugrawati; Ika Rezvani Aprita; Sri Agustina (PT. ROCE WISDOM ACEH, 2026)
Yellow coconut (Cocos nucifera L) is an underexplored variety with significant potential in the agricultural and food sectors. Unlike regular coconuts, yellow coconuts have a distinct yellow skin and sweeter water. This study evaluates the antioxidant activity of yellow coconut water and flesh using the DPPH (2,2-Diphenyl-1-Picrylhydrazyl) method, which measures the ability to neutralize free radicals. Results indicate that both yellow coconut water and flesh contain bioactive compounds with notable antioxidant properties, though their activities vary depending on concentration. The water showed significant antioxidant activity at higher concentrations, whereas the flesh showed better activity at lower concentrations. The IC50 values for yellow coconut water and flesh were 900.6 ppm and 1342 ppm, respectively, showing that while both parts have promising antioxidant potential, higher concentrations are needed for more effective results. This research provides valuable insights into the potential of yellow coconut as a natural antioxidant source and its implications for food and health product development.